Maqasid Al-Shari’ah Perspektif Abu Ishaq Al-Shatibi - Mohamad Ma’mun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
Imam al-Shatibi is one of usuliyyun (expert on the science of Usul fiqh) who can describe the concept of maqasid al-shari'ah systematically and in detail. Through his phenomenal masterpiece, Kitab al-Muwafaqat, he explained that shari’ah was passed down to humans solely for their welfare. The Book of Muwafaqat discusses general rules about human life, rules and limits that all humans are obliged to obey and carry out so that their lives are orderly and safe. People who practice shari’ah Islam are the freest and most calm people, because all the teachings, both small and large, contain maslahah for the man himself, even though he is not aware of it. Conversely, those who come out and disobey the rules will be bound and fettered by their lusts. Although they may look nice and pleasant, they are essentially loss and loss. Imam al-Shatibi dividing maslahah into three levels, namely the Needs Daruriyyah, Needs Hajjiyah, and Needs Tahsiniyyah.